The Role Moderating of E-Word of Mouth in the Relationship Between E-CRM and Customer Loyalty; Empirical Study Of Online Shopping - mohammed, omar (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2024)
The objective of this study is to measure to examine how E-Word of Mouth moderates the effect of E- CRM and Customer Loyalty in the context of online shopping in Istanbul. A correlational study design was adopted in this study to collect data (survey) from(430) participants distributed by Facebook Empirical results reveal that there is a significant and positive impact of E-Word of Mouth on Social CRM and customer loyalty behavior. This study contributes to closing the empirical gap in e-CRM and customer engagement research by providing support for consumer perception of E-Word of Mouth as a significant factor triggering customer loyalty with the brand post. This study also supplies a guide that e-CRM with E-Word of Mouth leads to customer loyalty to the brand without others